The influence of headmaster’s leadership and teacher motivation on teacher performance - Sumarlin Sumarlin; Bukman Lian; Syaiful Eddy (Global Econedu, 2021)
This research was motivated by the leadership of the principal, teacher work motivation and teacher performance that was not optimal.This study aims to find out whether or not 1) The influence of the headmaster's leadership on the teacher's performance, 2) The influence of teacher work motivation on teacher performance, 3) The influence of the headmaster's leadership and the motivation of the teacher's work together on the teacher's performance. This analysis uses the quantitative descriptive method. A sample of 64 civil servant teachers in the form of questionnaires at Junior High School in KayuagungSubdistrict, Ogan KomreringIlir Regency. Tools for data collecting in the form of questionnaires. The analysis method used the partial and simultaneous correlation test method using SPSS software version 26.0. The results of this study showed, 1) The leadership of the headmaster has a major impact on the success of teachers with a score of tCount7,720 and ttable 1,998, 2) there is a significant influence of teacher work motivation on teacher performance with valueof tCount8.729 and ttable 1,998,3) there is a significant influence of the headmaster's leadership and the motivation of the teacher's work on the performance of the teacher with theFCount50,396 danFtable 3,150. The conclusion is that there is a major impact on the success of teachers at Junior High School in Kayuagung Subdistrict, Ogan Komering Ilir Regency from the leadership and encouragement of the headmaster for the teacher's job.